1994
DOI: 10.1042/cs0870593
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density and Mineral Metabolism in Thyroidectomized Patients Treated with Long-Term l-Thyroxine

Abstract: 1. A decreased bone mass has been reported in patients with endogenous hyperthyroidism, but the effect on bone density and mineral metabolism of thyroxine administration in thyroidectomized patients is still controversial. To further contribute to this debate, we studied 25 women thyroidectomized for thyroid cancer on long-term treatment with thyroid-stimulating hormone-suppressive doses of L-thyroxine. Twenty-one sex- and age-matched normal subjects were also studied as a control group. 2. The bone density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 0 publications
2
42
0
2
Order By: Relevance
“…Among premenopausal women, the effect does not appear to be significant (Marcocci et al 1994). Furthermore, individual studies reported both accelerated BMD loss (Kung et al 1993, McDermott et al 1995, increased risk of hip fractures (Quan et al 2002) and no effect (Franklyn et al 1992, Giannini et al 1994, Marcocci et al 1994, Muller et al 1995, Rosen et al 1998) in a similar number of reports. Thus, the quality of evidence on the strength of the association between serum TSH and BMD reported in the American Medical Association guidelines for diagnosis and management of subclinical thyroid disease was negative, or only fair in postmenopausal women with a history of overt hyperthyroidism (Surks et al 2004).…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…Among premenopausal women, the effect does not appear to be significant (Marcocci et al 1994). Furthermore, individual studies reported both accelerated BMD loss (Kung et al 1993, McDermott et al 1995, increased risk of hip fractures (Quan et al 2002) and no effect (Franklyn et al 1992, Giannini et al 1994, Marcocci et al 1994, Muller et al 1995, Rosen et al 1998) in a similar number of reports. Thus, the quality of evidence on the strength of the association between serum TSH and BMD reported in the American Medical Association guidelines for diagnosis and management of subclinical thyroid disease was negative, or only fair in postmenopausal women with a history of overt hyperthyroidism (Surks et al 2004).…”
Section: Introductionmentioning
confidence: 71%
“…Some authors described decreased BMD in pre-and postmenopausal women with a significant negative correlation with T3 levels (Tauchmanova`et al 2004). In other reports only postmenopausal women were affected (Faber & Galloe 1994) or no diminution was observed (Franklyn et al 1992, Giannini et al 1994, Marcocci et al 1994, Muller et al 1995, Rosen et al 1998. With respect to hyperthyroidism due to suppressive LT4 treatment, some trials included premenopausal women with little or no change in BMD between controls and long-term treated patients (Franklyn et al 1992, Giannini et al 1994, Marcocci et al 1994, Muller et al 1995.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations